The current place of direct oral anticoagulants in the prevention/treatment of venous thromboembolism - Tomić, Maja (Archives of Pharmacy, 2020)
Venous thromboembolism (VTE; includes deep venous thrombosis, DVT, and pulmonary embolism, PE) represents the third most common acute cardiovascular syndrome. Contemporary VTE management comprises primary prevention in high-risk patients, treatment of established VTE, and prevention of its recurrence (secondary prevention). Anticoagulants are the basis of VTE pharmacological prophylaxis and treatment. For several decades, parenteral (heparin and low-molecular-weight heparins, LMWHs) and oral anticoagulants (vitamin K antagonists, VKAs) have been the cornerstone of VTE prevention/treatment. The introduction of direct oral anticoagulants (DOACs: thrombin inhibitor dabigatran and Xa inhibitors rivaroxaban, apixaban, edoxaban, and betrixaban) markedly improved the management of VTE by overcoming many disadvantages of conventional anticoagulants. For primary VTE prevention in patients after total hip/knee arthroplasty, rivaroxaban, apixaban, and dabigatran are preferred over LMWHs, due to comparable efficacy and safety, but favourable acceptability (avoided everyday injections). In other high-risk populations (other surgical patients, acutely ill medical patients), LMWHs are still the recommended option. Betrixaban is currently the only DOAC approved for VTE prophylaxis in medically ill patients during and after hospitalization. For acute VTE treatment and secondary prevention, DOACs (rivaroxaban, apixaban, edoxaban, and dabigatran) are recommended as the first-line therapy in the general population. DOACs proved to be similarly effective but safer than VKAs. In some specific populations, DOACs also seem to be advantageous over conventional treatment (patients with renal impairment, elderly, long-term secondary prevention in cancer patients). Currently, there is no data from randomized head-to-head comparative studies between the DOAC classes or representatives so the choice is made mainly according to patient characteristics and pharmacokinetic properties of the drug.
Keywords: direct oral anticoagulants (DOACs); venous thromboembolism (VTE); deep vein thrombosis (DVT); pulmonary embolism (PE)